Measuring the pass-through of the reference policy rate to deposit rates in Argentina - D'Amato, Laura Inés (2019)
Using a panel-time series approach that allows for heterogeneity, we study the pass-through of the policy reference rate to time deposit rates using high frequency data. We also evaluate the impact of the introduction of a new modality of online time deposit contracts in April 2019 on the transmission of the central bank reference policy rate to time deposit rates offered by banks in Argentina. We find that there is an incomplete long run pass-through in both the corporate and household segments of the deposits market. The results also indicate that the implementation of the new modality, aimed at stimulating more competition for funds between banks, led to a significant increase in the responsiveness of bank time deposit rates to movements in the reference policy rate, particularly in the corporate segment of the market.